Cooperation between Mind, Body and Soul during Trauma: Array - Susanu, Neaga (New Trends in Psychology, 2021)
Although theoretically we humans belong to an extremely powerful species, resisting over time endless wars, natural or man-made disasters, losses, violence and personal betrayals, all these traumatic experiences have left traces both at the level of history and at the personal or family level. At the same time, these traces are permeated in our minds and emotions- in our ability to enjoy and experience happiness and even on the immune system and our biology. Trauma affects not only those directly involved but also those around them (over whom extra pressure is exerted, namely to give them their energy and strength in their desire to help them continue to function, despite being overwhelmed by the memory of the pain and shame of having been through those traumas.